2021
DOI: 10.1007/s42399-021-01033-9
|View full text |Cite
|
Sign up to set email alerts
|

Response to Commentary: Fungal Infections of Oral Cavity: Diagnosis, Management, and Association with COVID-19

Abstract: This letter is a response to commentary by Ambadasu et al. on a review article by Santosh et al. on “Fungal Infections of Oral Cavity: Diagnosis, Management, and Association with COVID-19.” In their commentary, Ambadasu et al. mentioned that in the list of COVID-19 associated fungal infections, mucormycosis should be added. In this response, we provide our thoughts on including mucormycosis in COVID-19 associated fungal infections of the oral cavity. We conclude that mucormycosis surge was more prevalent durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 3 publications
1
23
0
Order By: Relevance
“…Oral microbiome is quiet diverse and is comprised of over 700 different “core” and “Transient” microbial species including Gram-positive, Gram-negative and fungal species [ 1 ], which significantly contribute towards gingivitis, periodontitis, dental caries, stomatitis, and candidiasis [ 2 ]. This greater microbial load is influenced by several factors including host, signaling systems, and environmental factors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral microbiome is quiet diverse and is comprised of over 700 different “core” and “Transient” microbial species including Gram-positive, Gram-negative and fungal species [ 1 ], which significantly contribute towards gingivitis, periodontitis, dental caries, stomatitis, and candidiasis [ 2 ]. This greater microbial load is influenced by several factors including host, signaling systems, and environmental factors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Oral infections such as oral candidiasis and periodontal disease is a series of polymicrobial infection that affect the oral mucosa and tooth root [1]. Deterioration of oral hygiene leads to intraorally colonization of fungi or bacteria, it has been reported to contribute to systemic diseases such as gingivitis, aspiration pneumonia, deep mycosis, or increased severity and mortality in the historical pandemic of corona virus disease-19 (COVID-19) [2][3][4]. It is suggested that aspiration pneumonia, which is often seen in the elderly, is caused by oral bacteria growing in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Candidiasis has been increasing in recent decades, mainly due to the growing number of individuals with immunocompromised conditions and the higher antifungal resistance of Candida spp. [1]. Candida spp.…”
Section: Introductionmentioning
confidence: 99%
“…is the most common fungus, oral candidiasis (OC) is particularly critical due to its high prevalence in all ages and genders [3]. OC is characterized by oral discomfort, pain, burning sensation, parageusia, and aversion Antibiotics 2023, 12, 797 2 of 19 to food [1,4]. It is usually associated with age (childhood or older), smoking, diabetes mellitus, nutritional disorders, endocrinopathies, immunosuppressive conditions, and malignancies [4].…”
Section: Introductionmentioning
confidence: 99%